Correction: Analysis of 1-aminoisoquinoline using the signal amplification by reversible exchange hyperpolarization technique. Issue 2 (26th November 2020) - Jeong, Hye Jin; Min, Sein; Jeong, Keunhong
Abstract : Correction for 'Analysis of 1-aminoisoquinoline using the signal amplification by reversible exchange hyperpolarization technique' by Hye Jin Jeong et al., Analyst, 2020, 145, 6478–6484. DOI: ; 10.1039/D0AN00967A .